PENGARUH BUDAYA ETIS ORGANISASI DAN ORIENTASI ETIKA TERHADAP SENSITIVITAS ETIKA (Studi Empiris Tentang Pemeriksa Internal Bawasda Kabupaten Mojokerto) - Cindy Ariana Oliviantika; Noor Shodiq Askandar; M. Cholid Mawardi (Universitas Islam Malang, 2021)
The purpose of this study was to obtain, determine the effect of organizational ethical culture, ethical orientation, on ethical sensitivity to the performance of local government agencies. The case study in this research is the Mojokerto district work unit. The sample of this study used a purposive sampling method and the sample used in this study was 35 respondents. This study used multiple regression analysis using quantitative methods. The results of this study simultaneously variable organizational ethical culture (X1), ethical orientation variable (X2) and ethical sensitivity variable (Y) simultaneously have a positive effect on the performance of Local Government AgenciesKeyword: norms, ethics, organizational ethical culture, ethical orientation, ethical sensitivity.